Performance analysis of reduced switch hybrid cascaded multilevel inverter with PSO-based PI controller during load variations - Nordin, M. Izzat; Leong, Ying Foo; Muhammad Hazarul Azmeer, Ab Malek; Suliana, Ab Ghani; Nur Huda, Ramlan (Kyushu University, 2024)
This paper presents the design and simulation of a Hybrid Multilevel Inverter (HMLI) optimized for reduced switch count and minimized total harmonic distortion (THD), while maximizing output voltage. The proposed HMLI configuration employs four voltage sources and five MOSFET switches, achieving peak-to-peak output voltage of 135V at a modulation index of 0.9. The harmonic minimization is accomplished using an LC filter and Alternate Phase Opposition Disposition (APOD) PWM technique. The performance evaluation, including analysis under no-load to fullload conditions as well as half-load to full load conditions, demonstrates that Particle Swarm Optimization-based PI (PSO-PI) controller significantly enhances system performance, maintaining nominal load output of 149.8 V with a THD of 2.23%. Under varying load conditions, the HMLI with PSO-PI controller shows a 5.23% THD and 147.58μs response time, compared to ZN-PI controller. The results demonstrate that HMLIs with PSO-PI controller offers enhanced voltage regulation, reduced harmonic distortion and rapid dynamic response during load transition.